Neoadjuvant versus adjuvant ipilimumab plus nivolumab in macroscopic stage III melanoma. (November 2018) - Blank, Christian; Rozeman, Elisa; Fanchi, Lorenzo; Sikorska, Karolina; Wiel, Bart; Kvistborg, Pia; Krijgsman, Oscar; Braber, Marlous; Philips, Daisy; Broeks, Annegien; Thienen, Johannes; Mallo, Henk; et al.
Abstract Adjuvant ipilimumab (anti-CTLA-4) and nivolumab (anti-PD-1) both improve relapse-free survival of stage III melanoma patients1, 2 . In stage IV disease, the combination of ipilimumab + nivolumab is superior to ipilimumab alone and also appears to be more effective than nivolumab monotherapy3 . Preclinical work suggests that neoadjuvant application of checkpoint inhibitors may be superior to adjuvant therapy4 . To address this question and to test feasibility, 20 patients with palpable stage III melanoma were 1:1 randomized to receive ipilimumab 3 mg kg−1 and nivolumab 1 mg kg−1, as either four courses after surgery (adjuvant arm) or two courses before surgery and two courses postsurgery (neoadjuvant arm). Neoadjuvant therapy was feasible, with all patients undergoing surgery at the preplanned time point. However in both arms, 9/10 patients experienced one or more grade 3/4 adverse events. Pathological responses were achieved in 7/9 (78%) patients treated in the neoadjuvant arm. None of these patients have relapsed so far (median follow-up, 25.6 months). We found that neoadjuvant ipilimumab + nivolumab expand more tumor-resident T cell clones than adjuvant application. While neoadjuvant therapy appears promising, with the current regimen it induced high toxicity rates; therefore, it needs further investigation to preserve efficacy but reduce toxicity. Neoadjuvant combination immunotherapy in patients with advanced melanoma shows favorable activity over adjuvant treatment and warrants future evaluation with modified dosing schedules to reduce treatment-related adverse events.